Comprehensive Study on Underslung Girder Bridge under Different Loading Conditions - Ieva Misiūnaitė; Algirdas Juozapaitis; Alfredas Laurinavičius (The Baltic Journal of Road and Bridge Engineering)
The comprehensive study on the structural behaviour of underslung girder bridge is examined in this study through both numerical modelling and experimental 3D model tests. The structural design of steel bridges in many cases is governed by their ability to withstand asymmetric loading conditions. Three different symmetric and asymmetric load cases were investigated to capture the deformational and flexural response of the main girder. It was found that under distributed load the structural response of underslung girder bridge was similar to beam-column with intermediate elastic supports. The numerical model was validated against experimental data with good agreement perceived, allowing an extensive parametric study to be performed. The observed influence of initial geometric imperfections and nonlinearities are discussed. It was found that symmetric load governs the ultimate limit state. However, the asymmetric one takes over in the case of serviceability. Finally, the study presented herein summarises experimental investigations, numerical simulations and design proposals obtained through the recent few years research program, carried on to deepen the knowledge on the structural behaviour of underslung girder bridges.